(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
This article gives an outline of the advancement of ideas of time in phonetics from the finish of the XIX century to the current day, during which the job of the emotional considers their development is uncovered. The article endeavors to respond to the inquiries, of what time is reflected in semantic time, and which job is played by the emotional (human) and calculate the formation of phonetic models of the time.